ROLES OF INFLUENCER ON CONSUMER PURCHASE INTENTION TOWARDS FASHION PRODUCTS IN BATAM - Edy Yulianto Putra; Kelly Tan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
In digital era nowadays, social media influencer holds an important role in influencing consumer’s opinion towards certain products. In this study, the author will analyze the impacts of influencer credibility’s on consumer purchase intention towards fashion products in Batam. The research data was obtained through distributing google form questionnaire with the condition that respondents follows at least one influencer on any social media platform. The total sample used in this study is 270 respondents who currently live in Batam.